Self-Reported Knee Function Can Identify Athletes Who Fail Return-to-Activity Criteria up to 1 Year After Anterior Cruciate Ligament Reconstruction: A Delaware-Oslo ACL Cohort Study - David Logerstedt; Stephanie Di Stasi; Hege Grindem; Andrew D. Lynch; Ingrid Eitzen; Lars Engebretsen; May Arna Risberg; Michael J. Axe; Lynn Snyder‐Mackler (2014)
Study Design Cohort study, cross-sectional. Objectives To determine if self-reported knee function assessed with the International Knee Documentation Committee 2000 Subjective Knee Form (IKDC 2000) could discriminate between successful and nonsuccessful performance on return-to-activity criteria (RTAC) tests after anterior cruciate ligament (ACL) reconstruction. Background Selecting appropriate performance-based and patient-reported tests that can detect side-to-side asymmetries, assess global knee function, and determine a participant's readiness to return to activity after ACL reconstruction can be a challenge for rehabilitation specialists. A simple tool or questionnaire to identify athletes with neuromuscular impairments or activity limitations could provide rehabilitation specialists with crucial data pertinent to their patients' current knee function and readiness to return to higher-level activities. Methods One hundred ninety-four level I and level II athletes who underwent ACL reconstruction participated in the study. One hundred fifty-eight athletes at 6 months after ACL reconstruction and 141 of the athletes at 12 months after ACL reconstruction completed a battery of functional tests to determine readiness to return to activity and the IKDC 2000 to determine self-reported knee function. For each athlete, status on the RTAC test battery was dichotomized into “passed” or “failed,” and status on the IKDC 2000 scores was dichotomized into “within” or “below” age- and sex-matched normal ranges. Comparisons were made between status on the RTAC test battery and the IKDC 2000 using chi-square tests. Accuracy statistics were also calculated. Results Six months after ACL reconstruction, 112 athletes (70.9%) failed RTAC and 76 (48.1%) were classified as having self-reported knee function below normal ranges. Among the 76 participants with IKDC 2000 scores below normal ranges, 69 (90.8%) failed the RTAC test battery (P<.001). However, among the 82 participants whose IKDC 2000 scores were within normal limits at 6 months, only 39 (47.6%) passed the RTAC test battery (P = .74). Twelve months after ACL reconstruction, 67 athletes (47.5%) failed RTAC and 31 (22.0%) had knee function below normal ranges. Among the 31 participants with IKDC 2000 scores below normal ranges, 25 (80.6%) failed the RTAC test battery (P<.001). However, among the 110 participants whose IKDC 2000 scores were within normal limits at 12 months, only 68 (61.8%) passed the RTAC test battery (P = .017). Conclusion The IKDC 2000 may be a clinically relevant tool to determine the timeliness or necessity of RTAC testing. For scores obtained 6 and 12 months after ACL reconstruction, low IKDC 2000 scores were reasonably indicative of failure on the RTAC test battery, whereas normal IKDC 2000 scores were not predictive of passing scores on the RTAC test battery. Level of Evidence Diagnosis, level 4. J Orthop Sports Phys Ther 2014;44(12):914–923. Epub 27 October 2014. doi:10.2519/jospt.2014.4852